NAFKAH BERKELANJUTAN PETANI SUKU DANI BERBASIS NATURAL CAPITAL DI KAMPUNG KALISEMEN DISTRIK NABIRE BARAT KABUPATEN NABIRE - Liborang, Hans F.; Roy, Marloza; Ramandey, Johanes M. (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2024)
The aim of this research is to determine the sustainable livelihood of Dani tribal farmers based on natural capital in Kalisemen Village, West Nabire District, Central Papua Province. This research approach was carried out using a qualitative approach and the type of research was descriptive research. The data used in this research are primary data and secondary data. Data collection was carried out using the triangulation method in the form of observation, interviews and documentation. Qualitative data analysis is carried out continuously, consisting of data collection, data analysis, data reduction, where the data is processed by carrying out three stages of activities and carried out simultaneously, namely data reduction, data presentation and conclusions through data verification. The results of this research show that the sustainable livelihood of the Dani tribe community in Kalisemen Village is based on natural capital using a multiple cropping system and also planting time patterns to maintain stable livelihoods in the form of cash with financial capital. capital) as well as improving the quality of children's education in the form of human capital as well as maintaining their social capital